If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 10 + -3 Combine like terms: 10 + -3 = 7 y = 7 Solving y = 7 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 7
| 5x+19x-9=6(4x+1) | | (3x+2)+(4x-5)=39 | | 2400=1*x^78 | | -7x-1=4x-89 | | 8b+5-6b=3 | | 2x+12+4x+18=66 | | 8b+12=8+7b+4 | | -40x^2+62x+63=0 | | -4(11a-6)+9(4+2a)=x | | y=10-3(x*2) | | -5y+18=4y | | 20=x-((x*.05)+1) | | 9-(x+6)=4x-7 | | 2x+12v+4x+18=66 | | (2x+8)+(3x+17)=5y+17 | | 2x-60=570 | | 7.5x15x1/2 | | -x=3x+2 | | x=x-(.05x+1) | | 5n+8+6=21 | | 5-104=8(p-8) | | 4w+16=2w+10 | | -(-2+8r)=6-15r | | 9(c+1)=8c-6 | | 4x-2x=570 | | -4.4z+5.9=-4.9z+2.9 | | 120=15/1/2 | | 3(x-1)-2(3x+2)=5(1-x) | | 1+3(-5z-3)=-5(5z+6)+3 | | w-3x-2y+2z=0 | | 4x15x1/2 | | 31y-(-1+10y)=-20 |